Menggali hukum perkawinan yang melakukan kecurangan - Arini, Nusra; Asmuni, Asmuni; Yuslem, Nawir (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Marriage registration is important for the validity of a marriage because it will provide legal protection and guarantee the rights arising from marriage. Marriages with falsified registration as in this study are sirri marriages where the husband and wife consciously take legal action in the form of forging marriage books. This paper describes the problems, firstly marital status with its falsified recording from the perspective of positive law and Islamic law. Second, the judge's legal considerations. Third, legal protection of rights arising from marriages without registration. The research method used is analytical descriptive. The results of the study show that: First, marital status with falsified records from the perspective of positive law and Islamic law (in this case the Compilation of Islamic Law) is valid and has legal force. However, there are negative implications for the non-fulfillment of the wife's rights as a result of divorce, if the excerpt of a marriage certificate that has been decided by the District Court has no legal force/fake is used as evidence in a divorce case at the Religious Court. Second, the Judge at the Religious Court in his legal considerations stated that even though the marriage certificate was fake, this certificate was made consciously and is known together. The Mataram District Court Judge in his legal considerations was a decision regarding an alleged unlawful act in the form of a fake marriage certificate, not a decision that annulled the marriage. As for marriages carried out without registration, the state cannot provide legal protection unless there is material truth that can be proven in court.